2003
DOI: 10.1038/sj.hdy.6800281
|View full text |Cite
|
Sign up to set email alerts
|

Associations between single nucleotide polymorphisms in candidate genes and growth rate in Arctic charr (Salvelinus alpinus L.)

Abstract: We tested for associations between single nucleotide polymorphisms (SNPs) in five candidate genes allied with the growth hormone axis and the age-specific growth rate of Arctic charr (Salvelinus alpinus L.: Salmonidae). Two large full sib families (N ¼ 217 and 95) were created by backcrossing males that were hybrids between two phenotypically divergent populations from Labrador, Canada and from Nauyuk Lake, Canada to females that were from Nauyuk Lake. Measures of individual growth rate (wet weight and fork le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 39 publications
2
71
1
3
Order By: Relevance
“…There are some candidate genes associated with growth in different species of fish such as the growth hormone (GH) (Blanck et al, 2009;De-Santis and Jerry, 2007), insulin-growth factor I (IGF-1) (De-Santis and Jerry, 2007;Thompson et al, 2010), and myogenin (MyoG) (Ulloa et al, 2013;Zou and Liu, 2015) genes, which were selected for this work. The growth hormone plays an important role in the stimulation of somatic growth in teleost (Tao and Boulding, 2003), while IGF-I is a mediator of the endocrine action of hormonal growth and is able to stimulate the synthesis of DNA and subsequent cell division in many cell types (Wood et al, 2005). Myogenin belongs to the family of myogenic regulatory factors: MRF (MyoD, Myf-5, Myogenin, and MRF-4); this gene is a specific transcription factor in muscle basic-helix-loop-helix involved in coordination of skeletal muscle development and also participates in the myogenesis and its repair (Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There are some candidate genes associated with growth in different species of fish such as the growth hormone (GH) (Blanck et al, 2009;De-Santis and Jerry, 2007), insulin-growth factor I (IGF-1) (De-Santis and Jerry, 2007;Thompson et al, 2010), and myogenin (MyoG) (Ulloa et al, 2013;Zou and Liu, 2015) genes, which were selected for this work. The growth hormone plays an important role in the stimulation of somatic growth in teleost (Tao and Boulding, 2003), while IGF-I is a mediator of the endocrine action of hormonal growth and is able to stimulate the synthesis of DNA and subsequent cell division in many cell types (Wood et al, 2005). Myogenin belongs to the family of myogenic regulatory factors: MRF (MyoD, Myf-5, Myogenin, and MRF-4); this gene is a specific transcription factor in muscle basic-helix-loop-helix involved in coordination of skeletal muscle development and also participates in the myogenesis and its repair (Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The associations between growth traits and polymorphisms in candidate genes of the somatotropic axis have been investigated in several fish species (Gross and Nilsson, 1999;Li et al, 2009b;Reinecke et al, 2005;Tao and Boulding, 2003). However, no study on association between polymorphisms in PSSs and growth traits is reported in fish studied to date.…”
Section: A B Cmentioning
confidence: 99%
“…Moreover, GHRH polymorphisms were associated with the average daily gain and fat thickness in pigs, which confirmed the potential usefulness of GHRH in marker-assisted selection programs (Franco et al, 2005). Meanwhile, sequence variation in the PACAP gene could affect growth hormone secretion, thus indirectly affecting growth and condition traits, which may explain the strong association of the SNP genotype GHRH/PACAP with early growth (Tao and Boulding, 2003). Recent studies have documented that the level of hormones in the GH axis can be used as a marker of growth performance in teleost fish.…”
Section: Microsatellite Polymorphism In Half-smooth Tongue Sole Ghrh mentioning
confidence: 99%